Modelization of the spatial distribution of corn head smut (Sporisorium reilianum Langdon and Fullerton) in Mexico - Sanchez-Pale, J.R.; Ramirez-Davila, J.F.; Gonzalez-Huerta, A.; de Leon, C. (Spanish Journal of Agricultural Research, 2011)
Sporisorium reilianum has caused significant economical damages in Mexico, in temperate and relatively dry areas, where maize is cultivated. The knowledge about the spatial distribution of this pathogen is basic to elaborate integrated management programs, and precise and efficient the development of sampling methods and control techniques. Unfortunately, in Mexico there are no studies on spatial behavior of this disease. For this reason, this study was developed to model S. reilianum spatial distribution by the year 2008; and also, to establish its spatial behavior with geostatistics techniques. The sampling method established 100 points for each of 30 locations of 27 municipalities in the State of Mexico. In each point, 500 plants were counted and those presenting symptoms of the disease were recorded. A geostatistical analysis was done in order to estimate the experimental semivariograms. It was adjusted to theoretical models (spherical, exponential or gaussian) with the program Variowin 2.2; later, it was evaluated through the crossed validation with the geostatistical interpolation method or kriging. Finally, aggregation maps of the disease were elaborated. The disease was found in 30 sampled locations; all of them presented an aggregated spatial pattern of the disease. Twenty one locations were adjusted to the spherical model, five to the exponential model and two to the Gaussian model. Aggregation maps were established in all models. It was observed that S. reilianum was not uniform in the assess areas. Results showed the spatial distribution of S. reilianum and real infestation in field using geostatistical techniques.